Healthcare professionals' perspectives of providing end-of-life care for infants, children and young people in acute settings: A multi-site qualitative study - McLorie, Emma Victoria; Hackett, Julia; Barrett, Laura; Peat, George; Weatherly, Helen; Hinde, Sebastian; Walker, Gabriella; Noyes, Jane; Oddie, Sam; Vasudevan, Chakrapani; Feltbower, Richard G; Phillips, Bob; et al. (Palliative medicine, 2025)
Paediatric end-of-life care is an important part of palliative care, and provides care and support for children in the last days, weeks, months or year of life. However, there is currently a picture of inconsistent and disjointed provision. Despite differences in delivery models across countries and cultures, healthcare professionals need to be able to support families through this difficult time. However, there is limited evidence to base high quality end-of-life care. To explore healthcare professionals' experiences of delivering end-of-life care to infants, children and young people, their needs and the factors affecting access and implementation. Qualitative study employing online focus groups, analysed using framework analysis. Healthcare professionals who provided end-of-life care to infants, children and young people, across cancer centres and neonatal and paediatric intensive care units. A total of 168 professionals from 13 tertiary hospitals participated in 23 focus groups. Three themes highlighted many barriers to delivering optimal care: (1) ; (2) and (3) . These illustrate professionals' awareness and desire to deliver high-quality care, yet are constrained by a number of factors, suggesting the current system is not suitable. This study provides an in-depth exploration of paediatric end-of-life care, from those professionals working across the settings accounting for the majority of end-of-life care delivery. Many of these issues could be resolved by investment in: funding, time, education and support to enable delivery of increasingly complex end-of-life care.